2022
DOI: 10.1002/cne.25435
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of cellular physiology and morphology of Purkinje cells in the adult zebrafish cerebellum

Abstract: This study was designed to explore the functional circuitry of the adult zebrafish cerebellum, focusing on its Purkinje cells and using whole-cell patch recordings and single cell labeling in slice preparations. Following physiological characterizations, the recorded single cells were labeled for morphological identification. It was found that the zebrafish Purkinje cells are surprisingly diverse. Based on their physiology and morphology, they can be classified into at least three subtypes: Type I, a narrow sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 110 publications
(285 reference statements)
0
5
0
Order By: Relevance
“…At least two molecularly distinct subpopulations of ECs have been identified: olig2 + and calb2b + ECs, each occupying distinct regions in the dorsoventral and mediolateral axes of the cerebellum, with the 156A gal4 line that we used in this study, labeling both olig2 + and olig2 - populations (McFarland et al, 2008; Bae et al, 2009; Takeuchi et al, 2015). Zebrafish ECs have also been shown to have diverse dendritic morphology and projection patterns and the projection targets of ECs correlate with their location within the cerebellum, suggesting a molecular code for the topographic organization of different EC types (Heap et al, 2013; Magnus et al, 2023). We do not yet know if the chatty and stuttering types we observe correspond to these molecularly and topographically distinct populations of ECs but such heterogeneity in EC populations will not be surprising.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…At least two molecularly distinct subpopulations of ECs have been identified: olig2 + and calb2b + ECs, each occupying distinct regions in the dorsoventral and mediolateral axes of the cerebellum, with the 156A gal4 line that we used in this study, labeling both olig2 + and olig2 - populations (McFarland et al, 2008; Bae et al, 2009; Takeuchi et al, 2015). Zebrafish ECs have also been shown to have diverse dendritic morphology and projection patterns and the projection targets of ECs correlate with their location within the cerebellum, suggesting a molecular code for the topographic organization of different EC types (Heap et al, 2013; Magnus et al, 2023). We do not yet know if the chatty and stuttering types we observe correspond to these molecularly and topographically distinct populations of ECs but such heterogeneity in EC populations will not be surprising.…”
Section: Discussionmentioning
confidence: 99%
“…DCNs are known to be heterogenous with respect to their projection patterns, molecular expression patterns, firing properties and transmitter phenotypes. While DCNs consist of glutamatergic, GABAergic and glycinergic neurons (Bagnall et al, 2009; Uusisaari and Knöpfel, 2012; Kebschull et al, 2024), no inhibitory subtypes have been identified among ECs in teleosts and they seem to be a fully glutamatergic, long range projecting neuronal class (Bae et al, 2009; Heap et al, 2013; Matsui et al, 2014; Takeuchi et al, 2015; Harmon et al, 2020; Magnus et al, 2023). Given the above, one might speculate that distinct EC populations in fish might be related to ancestral glutamatergic populations observed in amniotes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations